Personal Qualities in The Structure of The Subject of Pedagogical Activity - Akhmedova Aziza Akmalovna (Genius Journals, 2021)
The article considers about the general definition of the personality traits of a teacher, the professional and pedagogical qualities of the personality, personal orientation in the structure of the subject of pedagogical activity, professional self-awareness in the structure of the subject of pedagogical activity, the teacher as a subject of pedagogical work and the definition of pedagogical abilities.
Keywords: Personality Traits; Pedagogical Qualities; Professional Personality; Personal Orientation